Influence of Yttria on Oxide Dispersion Strengthened (ODS) Ferritic Steel. (2018) - Kumar, Deepak; Prakash, Ujjwal; Dabhade, V.V.; Laha, K.; Sakthivel, T.
Abstract: Oxide dispersion strengthened (ODS) ferritic steels are the most promising candidate materials for advanced fast breeder reactors of future. They exhibit excellent swelling, corrosion resistance and superior high temperature strength. Fe-18Cr-2W-0.2Ti-(0.3-0.5)Y2 O3 (all in wt.%) alloys were prepared by mechanical alloying of elemental powders in Zoz Simoloyer attritor. The mechanical alloyed powders were heated in hydrogen atmosphere at 1423K in a steel can. The can was hot forged in a 100ton friction screw forging press. Increase in yttria content from 0.3 to 0.5wt.% causes a decrease in ultimate tensile strength and ductility. Reasons for this are discussed. Observed properties are related with the microstructure.